Noise Improves Visual Motion Discrimination via a Stochastic Resonance-Like Phenomenon - Treviño, Mario; De la Torre-Valdovinos, Braniff; Manjarrez, Elias (Frontiers in Human Neuroscience, 2016)
The stochastic resonance (SR) is a phenomenon in which adding a moderate amount of noise can improve the signal-to-noise ratio (SNR) and performance of nonlinear systems. SR occurs in all sensory modalities including the visual system in which noise can enhance contrast detection sensitivity and the perception of ambiguous figures embedded in static scenes. Here, we explored how adding background white pixel-noise to a random dot motion (RDM) stimulus produced changes in visual motion discrimination in healthy human adults. We found that, although the average reaction times remained constant, an intermediate level of noise improved the subjects' ability to discriminate motion direction in the RDM task. The psychophysical responses followed an inverted U-like function of the input noise, whereas the incorrect responses with short reaction times did not exhibit such modulation by external noise. Moreover, by applying stimulus and noisy signals to different eyes, we found that the SR phenomenon occurred presumably in the primary visual cortex, where these two signals first converge. Our results suggest that a stochastic resonance-like phenomenon mediates the improvement of visual motion perception in the RDM task.